TINDAK TUTUR DALAM FILM PENDEK â€œCINTA DIBALIK AWANâ€ (KAJIAN PRAGMATIK) - Dwi Septiani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study aims to analyze speech actions in the short film Cinta Dibalik Awan by Umay Shahab. The analysis focuses on the analysis of speech actions. In the speaking action, there is a concrete form of speaking event where there is a message or message that the speaker wants to convey to the speaking partner. In this short film there are speech acts that are closely related to speech acts and speech events. The method used in this study is the qualitative descriptive method. The primary data for this study are eight statements between the two main figures, namely Jessica and Razi. The speech actions are divided into three speech actions, namely the location, the illocution and the perlocution. In addition, speech actions are reclassified using five speech actions, which are affirmative, directive, expressive, supervisory and declarative. The results of the research on speech actions in eight intermediate speech actions of the short film Cinta Dibalik Awan are six speeches included in the Guideline Speech Act and two speeches included in the expressive speech actions. The act of directive identified is the subject of the request and recommendation, while the act of expressive language that exists refers to anger.